STUDENTS' INTEREST IN READING SHORT STORIES USING THE KURTILAS STUDENT BOOK REVISED EDITION 2017 CLASS XI SMK GARUDA NUSANTARA - Saiful Muktiali; Listiani Indriyani Achmad; Nenda Nenda (Sean Institute, 2023)
Interest relates to the style of motion that encourages a person to face or deal with people, objects, activities and experiences that are stimulated by the activity itself. This study aims for research purposes, namely: to concretely find out students' interest in reading short stories through the 2017 revised edition of the Kurtilas student book in class XI SMK Garuda Nusantara Even Semester in 2022/2023. This research was conducted at Garuda Nusantara Vocational School Cikarang with a sample of class XI students at Garuda Nusantara Vocational School. The research method that the writer uses is descriptive method, namely research by describing the object of research at the current state of affairs based on the facts as they are, then analyzed and interpreted. The research instruments used were observations at the Garuda Nusantara Vocational School, interviews with Indonesian teachers and several students at the schools studied, as well as distributing questionnaires to class XI students at Garuda Nusantara Vocational School 2022/2023. In the process of this study the authors used descriptive data analysis to present the results obtained. The results of the study stated that students' interest in reading short stories was quite good especially with the encouragement and motivation from the subject teacher. Within one month they spend three or even more short story reading materials that they read, it's just that there are some of the students who have used the website to read short stories because teachers don't use the website for short story teaching materials.